Diversidade e conservação de anuros em áreas úmidas costeiras no sul do Brasil - Machado, Iberê Farina (Universidade do Vale do Rio dos Sinos, 2011)
Despite its great biological diversity, productivity and man-made values, most wetlands have been converted for agriculture or forestry, and the impact of anthropogenic changes on the anuran community is a strong limitation to programs for management and conservation of these ecosystems. This thesis aims to: 1) Gather information about how the isolation of coastal dunes wetlands affects the anuran distribution with different dependencies of water; 2) Investigate the effects of a patch of pine forest exotics (Pinus spp.) on the anuran assembly in wetlands in southern Brazil; and 3) Investigate how different management practices used by rice farmers affect the assembly of frogs. On a landscape scale, it is known that isolation reduces immigration rates and increases the chance of extinction; and the species-area relationship indicates that larger areas keep populations with greater numbers of individuals. In this study, anuran richness and composition in coastal lagoons were determined by a combination of isolation, habitat diversity and hydroperiod. Area did not influence the anuran richness and composition in the wetlands of coastal dunes. However, the continuous process of fragmentation and alteration of wetlands tends to increase isolation and reduce the diversity of habitats from wetlands, directly influencing the anuran species according to their degree of water dependence. As the influence of the pines, in general, natural wetlands had a higher richness, abundance and diversity than pine wetlands. This result indicates that the occurrence of pine affect negatively, mainly by reducing the hydroperiod, the anuran diversity in southern Brazil. The implementation of management programs that include removal of exotic pine trees in conservation areas in southern Brazil, such as Parque Nacional da Lagoa do Peixe, it is urgent to minimize the spread and impacts on the biodiversity. The different practices adopted by rice farmers after harvest (presence or absence of surface water) did not affect the richness and abundance of frogs, however, there was a significant change in anuran composition. The difference in species composition between the management practices adopted is an interesting result in terms of biodiversity conservation. As a new practice management of natural resources, rice farmers could keep part of their agricultural land flooded during the fallow phase, the increase of the mosaic of wet and dry areas can help to support a greatest diversity of amphibians. These findings should be taken into consideration for regional strategies for conservation of wetlands in southern Brazil, especially in programs for management of protected coastal wetlands of Rio Grande do Sul.
Keywords: Anuros; Biodiversidade; Rio Grande do Sul; Conservação; Biodiversity; Conservation; Frogs; ACCNPQ::Ciências Biológicas::Biologia Geral